Islam Nusantara and The Esense of Islam - Faisal, Faisal (JURNAL JAWI, 2018)
The Wali played a dynamic role in spreading Islam so that the religion can easily be accepted by the Indonesian people. The spread of Islam in the archipelago used several approaches or ways, including trade, marriage, sufism, educational, art and political. While at that time Indonesia was in the cultural vacuum of civilization due to the influence of two great kingdoms, the Hindu kingdom and Buddhist kingdom. Islam brought social and cultural changes which are refining and developing Indonesian culture. Adjustments between adat and sharia in various regions in Indonesia always occur, although sometimes, they face conflicts in local societies. Nevertheless, the process of Islamization in various places in Indonesia is carried out in a way that is acceptable to the local people. Thus, the religious life of the people, in general, shows a mix of elements of Islam and previous beliefs. This was done by Islamic disseminators because there had long been religions (Hindu-Buddhist) and animistic beliefs in Indonesia